Determinants of Thailand’s National Innovative Capacity - Yodudom, Suthasinee; Boonvorachote, Tanachote; Treesivattanakul, Krissana (Creative Business and Sustainability Journal, 2020)
The national innovative capacity is regarded as the national development tool for sustainable progress, through an economic development with a high growth rate. This research is aimed to study factors and to propose guidelines for increasing number of innovations in Thailand. This study has predominantly adopted research methods in determinants of national innovation capacity from Furman, Porter, and Stern (2002). In applying them into Thailand’s context, the methods have been modified by using numbers of international patents as criteria for measuring innovation. Secondary data of relevant factors were collected from 2000 to 2016 and analyzed by econometric model. Multiple regression models were applied for data analysis. The analysis shows meaningful contributing factors to Thai innovation development to include share of GDP spent on higher education, openness to international investment and research and development expenditure. These significant variables reflect that Thailand has the potential for innovation growth with support from the government acting as an important driver under the strategic policies in boosting Thailand’s potential for innovation. The emphasis is on share of GDP spent on higher education, which is considered as the main factor that Thailand can strengthen itself as well as lead to sustainable development. Integration of the four disciplines as part of all levels of education, namely science, technology, mathematics and engineering (STEM) are new learning approach to create personnel with knowledge that will help promote Thailand’s potential for sustainable innovation.